Safety and efficacy of canine gonadal tissue-derived mesenchymal stem cells for early myxomatous mitral valve disease - Jeung, Soyoung; An, Ju-Hyun; Kim, Sung-Soo; Youn, Hwa-Young (Frontiers in Veterinary Science, 2024)
IntroductionThis study explored the potential efficacy and safety of therapy with mesenchymal stem cells (MSC) derived from gonadal tissue to address the early stage of myxomatous mitral valve disease (MMVD), the predominant cardiac condition in dogs.MethodsSixteen dogs diagnosed with MMVD B1 were enrolled in this trial and assigned to either a control group (control group, n = 10) or a group that received MSC derived from gonadal tissue (treatment group, n = 6). In the treatment group, allogeneic MSC derived from gonadal tissue (1 × 106 cells/kg) were intravenously administered at monthly intervals for five or more sessions. Data were compared at baseline and at the endpoint 1-year intervals. The efficacy was assessed using echocardiography, thoracic radiography, NT-proBNP, and the duration from B1 diagnosis to B2 transition to evaluate its effect on MMVD stage progression. Safety was evaluated through physical examinations, blood tests, imaging studies, and monitoring of adverse events.ResultsAfter 1 year of observation, the control group exhibited deteriorating echocardiographic parameters, whereas the treatment group displayed no substantial differences between baseline and endpoint measurements. Notably, a statistically significant disparity was noted in the left atrial diameter (p < 0.05) and E-wave velocity (p < 0.05) between the two groups, indicating a favorable impact of MSC derived from the gonadal tissue on left atrial pressure. Additionally, in contrast to the control group, the treatment group demonstrated delayed progression to MMVD stage B2, enabling them to prolong their disease duration without requiring cardiac medication (p = 0.038). In quality of life (QoL) metrics following MSC treatment, appetite showed a statistically significant improvement, increasing from 4 to 4.83 (p < 0.05).DiscussionTreatment with gonadal tissue-derived MSCs significantly delayed MMVD stage progression, highlighting the broad potential of MSC derived from gonadal tissue for treating complex veterinary conditions.